Effects of microplastic fibers on Lates calcarifer juveniles: Accumulation, oxidative stress, intestine microbiome dysbiosis and histological damage. (December 2021) - Xie, Mujiao; Lin, Lang; Xu, Peng; Zhou, Weiguo; Zhao, Changsheng; Ding, Dewen; Suo, Anning
Highlights: Lates calcarifer effectively eliminated polyethylene fibers after ingestion. Fibers exposure induced oxidative stress. Fibers ingestion caused intestinal microbiome dysbiosis. Lactobacillus reuteri and L. intestinalis were sensitive to fibers exposure. Slight intestinal histological damage was found. Abstract: Microplastic fibers originating from fishing ropes and nets are persistent and ubiquitous marine environmental pollutants that pose potentially threat to the health of aquatic species. Therefore, assessing their potential effects on marine biota has become an urgent research topic. In this study, the fate of fibers ingested by L. calcarifer and its consequence on intestine health were analyzed. A total of 150 fish was fed with polyethylene (PE) fibers at 1% concentration for 56 days. Retention of fibers, oxidative stress indicator malondialdehyde (MDA), intestinal permeability indicator diamine oxidase (DAO), intestine microbiome modulation and histological damage were evaluated. The results indicated that the consumption of fibers-contained food did not influence the growth of the fish. Low retention of fibers was observed, indicating effective elimination of fibers from the body of the fish and no significant accumulation after successive exposure. However, intestine oxidative stress was observed, indicated by an up regulation of MDA level. Whereases, DAO level was not influenced by the treatment. Fiber exposure induced intestine microbiome dysbiosis by decreasing alpha diversity especially community richness and inhibiting the growth of Lactobacillus and short-chain fatty acid producing bacteria. Lactobacillus reuteri and L. intestinalis were inhibited significantly, we suggested they can be sensitive indicators for fibers toxicity evaluation in future studies. Slight intestinal damage was observed after the feeding period. We concluded that dietary exposure to PE fibers did not induce acute harm to L. calcarifer . However, chronic effects were observed after the feeding period, including oxidative stress, intestine microbiome alterations, and intestinal damage. These findings provide valuable data for ecological risks assessment of fishing rope fiber in the marine environment.